2022
DOI: 10.14710/ijred.2022.45180
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Oven and Solar Drying of Agricultural Residues and Food Crops

Abstract: The current study examined reduction of moisture from agricultural energy and food crops in a conventional oven to a solar dryer at various treatment periods at temperature between 40 ± 10 oC.  Sugarcane bagasse and Phragmites Australis had initial moisture of 50.8 % and 6.07 % by dry weight, respectively, with higher heating values (HHV) 6548.5 kJ/kg and 17653.02 kJ/kg respectively. The moisture content of bagasse and phragmites were decreased by 51.31% and 68.69% respectively using oven drying, while the moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…These sensors were connected to an Arduino UNO that was programmed to log data over time and measure the gas concentration. The volume of gas was measured using the water displacement method with properly calibrated acrylic cylinders with a length of 45 cm and a diameter of 3.6 cm at a room temperature of 28 • C ± 1 • C as per the method mentioned in earlier studies [28]. After the completion of the bioH 2 production reaction, the digestate (1200 mL) from the first reactor was mixed with 100 mL of cow dung and introduced into the second reactor to produce biogas under AD conditions for 25 days.…”
Section: Experimental Condition Of Biohythane Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sensors were connected to an Arduino UNO that was programmed to log data over time and measure the gas concentration. The volume of gas was measured using the water displacement method with properly calibrated acrylic cylinders with a length of 45 cm and a diameter of 3.6 cm at a room temperature of 28 • C ± 1 • C as per the method mentioned in earlier studies [28]. After the completion of the bioH 2 production reaction, the digestate (1200 mL) from the first reactor was mixed with 100 mL of cow dung and introduced into the second reactor to produce biogas under AD conditions for 25 days.…”
Section: Experimental Condition Of Biohythane Productionmentioning
confidence: 99%
“…If the pH is too high (alkaline), the enzymes responsible for bioH 2 production may become inactivated and cause a reduction in bioH 2 production [19]. Therefore, ideal pH levels for bioH 2 production vary depending on the type of microorganism used [28]. The influence of pH plays an important role in the reaction because changes in pH cause reaction imbalances that have an ultimate impact on the bioH 2 production.…”
Section: Bioh 2 Productionmentioning
confidence: 99%
“…After separation, the biodiesel was washed with warm water at 50 • C to remove the glycerol and other contaminants. Finally, the water-washed biodiesel was dried in a locally designed and fabricated solar cabinet dryer that has a capacity of 0.105 m 3 for 3 h to remove the moisture content [17]. The light meter measured the solar irradiance flux (W/m 2 ) falling on the solar collector attached to the dryer (ST1307 Standard Instruments, Hong Kong, China).…”
Section: Batch-scale Biodiesel Productionmentioning
confidence: 99%
“…It can, therefore, be concluded that drying is an important and demanding aspect of agricultural production [1] for food producers and livestock breeders. The parameters of drying agricultural crops [2,3] have been investigated to increase the efficiency of the process or to ensure a minimum impact on the nutritional content. Among the wide spectrum of agricultural crops, attention is paid to the drying of cereals [4,5], lemons [6], olive pomaces [7], eggplants [8] and corn.…”
Section: Introductionmentioning
confidence: 99%